INDUSTRI KERTAS MASA ABBASIYAH DAN PERANANNYA PADA KEMAJUAN PERADABAN ISLAM - Fitri Sari Setyorini (IAIN Bengkulu, 2022)
The triumph of Islamic history in the Middle Ages in the Abbasid dynasty. The dynasty that stood from 751-1258 in West Asia and 1259-1521 AD in Egypt is remembered as a historical period in Islamic history. The peak of glory can not only be seen through the physical remains but also the thoughts that went beyond its time so that the West also had to learn from the Islamic world at that time to be able to rebuild their civilization. One form of the development and glory of Islam at this time, but often escapes the discussion of historians, is the role of the paper industry in helping the development of government, thought and intellectual development of the Abbasids. This paper focuses on the history and development of the paper industry in the Abbasid era. Paper in this period was a solution to the limitations of expensive and limited media such as papyrus and parchment. The development of the paper industry in some parts of the Islamic world has helped in the preservation of historical records both in the aspect of government and in the development of science. The historical approach and method as well as literature study used in this study prioritized sources related to the research topic based on the stages of historical research which included heuristics, levers, analysis and historiography.Keywords: Abbasid, paper, Baghdad, science.